2023
DOI: 10.1039/d3ra02883f
|View full text |Cite
|
Sign up to set email alerts
|

A recent overview of surfactant–drug interactions and their importance

Abstract: Interactions between surfactants and drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Furthermore, it has been reported that surfactants usually increase the solubility of insoluble drugs in organic solvents or in water. Increased solubility, on the one hand, raises the degree of subcooling required for nucleus precipitation during microdroplet quenching and cooling, leading to finer crystals or even amorphous forms. On the other hand, it reduces the supersaturation degree of the microcrystal suspension, decreasing the driving force for the growth of fine particles.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been reported that surfactants usually increase the solubility of insoluble drugs in organic solvents or in water. Increased solubility, on the one hand, raises the degree of subcooling required for nucleus precipitation during microdroplet quenching and cooling, leading to finer crystals or even amorphous forms. On the other hand, it reduces the supersaturation degree of the microcrystal suspension, decreasing the driving force for the growth of fine particles.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous amphiphilic compounds have been extensively used in a variety of industries, including farming, food engineering, oil industry, environmental and biological areas, pharmaceutical technology, textiles, and metallurgy. [1][2][3][4][5][6][7][8][9][10] These molecules are composed of two parts: (i) a hydrophobic component that prefers oil to water and (ii) a hydrophilic component that prefers water to oil. Above their CMC, these amphiphilic compounds in an aqueous environment can form a molecular self-assembly, which is referred to as a micelle.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, antibiotics can disrupt the balance of microorganisms in aquatic environments, influencing the overall health of these ecosystems. , It is thus important to monitor and find possible ways to isolate these drugs from water sources using secondary techniques such as foam fractionation . Numerous works have been performed on removing or minimizing the antibiotic concentrations in water with the help of various techniques such as adsorption, , advanced oxidation processes, , membrane filtration, , biological treatment methods, , and using various surfactants. …”
Section: Introductionmentioning
confidence: 99%